Generalization of a quadratic transformation formula due to gauss

Research output: Contribution to journalArticle

Abstract

The aim of this research paper is to obtain explicit expressions of (1-x) -2 a 2 F 1 [ a, b 2b+f; - 4 x / (1 - x) 2] for j = 0, ± 1, ± 2. For j = 0, we have the well-known transformation formula due to Gauss. The results are derived with the help of generalized Watson's theorem. Some known results obtained earlier follow special cases of our main findings.

Original languageEnglish
Article number789519
JournalInternational Journal of Mathematics and Mathematical Sciences
Volume2012
DOIs
Publication statusPublished - 2012

Fingerprint

Transformation Formula
Gauss
Theorem
Generalization

ASJC Scopus subject areas

  • Mathematics (miscellaneous)

Cite this

@article{c304694e259c43a59b3f4ad53d43f8b3,
title = "Generalization of a quadratic transformation formula due to gauss",
abstract = "The aim of this research paper is to obtain explicit expressions of (1-x) -2 a 2 F 1 [ a, b 2b+f; - 4 x / (1 - x) 2] for j = 0, ± 1, ± 2. For j = 0, we have the well-known transformation formula due to Gauss. The results are derived with the help of generalized Watson's theorem. Some known results obtained earlier follow special cases of our main findings.",
author = "Rakha, {Medhat A.}",
year = "2012",
doi = "10.1155/2012/789519",
language = "English",
volume = "2012",
journal = "International Journal of Mathematics and Mathematical Sciences",
issn = "0161-1712",
publisher = "Hindawi Publishing Corporation",

}

TY - JOUR

T1 - Generalization of a quadratic transformation formula due to gauss

AU - Rakha, Medhat A.

PY - 2012

Y1 - 2012

N2 - The aim of this research paper is to obtain explicit expressions of (1-x) -2 a 2 F 1 [ a, b 2b+f; - 4 x / (1 - x) 2] for j = 0, ± 1, ± 2. For j = 0, we have the well-known transformation formula due to Gauss. The results are derived with the help of generalized Watson's theorem. Some known results obtained earlier follow special cases of our main findings.

AB - The aim of this research paper is to obtain explicit expressions of (1-x) -2 a 2 F 1 [ a, b 2b+f; - 4 x / (1 - x) 2] for j = 0, ± 1, ± 2. For j = 0, we have the well-known transformation formula due to Gauss. The results are derived with the help of generalized Watson's theorem. Some known results obtained earlier follow special cases of our main findings.

UR - http://www.scopus.com/inward/record.url?scp=84867760863&partnerID=8YFLogxK

UR - http://www.scopus.com/inward/citedby.url?scp=84867760863&partnerID=8YFLogxK

U2 - 10.1155/2012/789519

DO - 10.1155/2012/789519

M3 - Article

VL - 2012

JO - International Journal of Mathematics and Mathematical Sciences

JF - International Journal of Mathematics and Mathematical Sciences

SN - 0161-1712

M1 - 789519

ER -